CHARACTERIZATION OF FUNCTIONAL PROPERTIES FISH PROTEIN CONCENTRATE OF SKIPJACK ROE (Katsuwonus pelamis) - Frets Jonas Rieuwpassa; Joko Santoso; Wini Trilaksani (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2013)
By product that rich in protein such as fish roes are potential as raw material for protein concentrate. This research aimed to utilize skipjack roes to produce protein concentrate and to characterize its functional properties. The method used to extract protein was defatting method using isopropyl alcohol and ethanol with extraction times of 1, 2, and 3 hours.  The results showed that skipjack roes contained 19.81% of protein, 3.41% of fat, 71.32% of moisture, 2.04% of ash, and 1.53% of carbohydrate (by difference). Defatting method using isopropyl alcohol for 3 hours produced the best roe protein concentrate (RPC).  The product meets to the quality requirements of fish protein concentrate type B, contained protein and fat of 71.79% and 2.78%, respectively. This product also had functional properties as follows: water absorption capacity (1.57 ml/g), oil absorption capacity (1.82 g/g), emulsion capacity (81.65%), bulk density (0.51 g/ml), foaming capacity (1.90 ml), foaming stability (0.22 ml) and protein digestibility (95.86%).  Lysine and leucine became the major essential amino acid of RPC, with values were 70.76 and 64.91 mg/g protein, respectively. The composition of amino acids of RPC skipjack consisted of 8 essentials amino acids, 5 non-essentials amino acids and 2 semi-essentials amino acids. Keywords: extraction, fish roe skipjack, roe protein concentrate